Multi-target Direction Measurement on Bistatic MIMO Radar - Jingfang Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In recent years, multiple-input multiple output (MIMO) radar has been widespread concern in the domestic and foreign researchers. Bistatic radar draws on the great success of MIMO technology in the communications field, and it has many advantages over conventional radar. In this paper, the direction angles estimations of bistatic MIMO radar are researched. To contrast traditional radar DOA estimates, the direction vector of the bistatic MIMO radar is the Knonecker plot of  the emission vector and reception  vector, that two-dimensional direction angles is estimated. To solve this problem, the principle of bistatic MIMO radar signal model is in-depthly researched.By proposing Capon dimensionality reduction method, the two-dimensional directions of the dual-based MIMO radar are estimated,  and computer simulation is to verify the effectiveness of the method.  http://dx.doi.org/10.11591/telkomnika.v12i9.4602